2020
DOI: 10.1007/s00204-020-02672-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel 1-hydroxypyridin-2-one metal chelators prevent and rescue ubiquitin proteasomal-related neuronal injury in an in vitro model of Parkinson’s disease

Abstract: Ubiquitin proteasome system (UPS) impairment, excessive cellular oxidative stress, and iron dyshomeostasis are key to substantia nigra dopaminergic neuronal degeneration in Parkinson's disease (PD); however, a link between these features remains unconfirmed. Using the proteasome inhibitor lactacystin we confirm that nigral injury via UPS impairment disrupts iron homeostasis, in turn increasing oxidative stress and promoting protein aggregation. We demonstrate the neuroprotective potential of two novel 1-hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The derivatives 7c, 7g and 7k-l which already had exhibited good selectivity toward to ALR2 inhibition were tested for DPPH radical scavenging activity, as well as compound 7a serving as comparison. Interestingly, much superior to well-known antioxidant Trolox and reported deferiprone (3-hydroxy-1,2-dimethyl-1H-pyridin-4-one) [36], phenolic derivatives 7k-l showed excellent DPPH radical scavenging ability, revealing that the phenolic substituents might be a key structure enhancing DPPH free radical scavenging activity (Table 2). Particularly, at a concentration of 1 µM, compound 7l had most favorable antioxidant properties, achieving 41.48% of inhibition rate.…”
Section: Dpph Radical Scavenging Activitymentioning
confidence: 95%
“…The derivatives 7c, 7g and 7k-l which already had exhibited good selectivity toward to ALR2 inhibition were tested for DPPH radical scavenging activity, as well as compound 7a serving as comparison. Interestingly, much superior to well-known antioxidant Trolox and reported deferiprone (3-hydroxy-1,2-dimethyl-1H-pyridin-4-one) [36], phenolic derivatives 7k-l showed excellent DPPH radical scavenging ability, revealing that the phenolic substituents might be a key structure enhancing DPPH free radical scavenging activity (Table 2). Particularly, at a concentration of 1 µM, compound 7l had most favorable antioxidant properties, achieving 41.48% of inhibition rate.…”
Section: Dpph Radical Scavenging Activitymentioning
confidence: 95%
“…The kinetics of reaction suggested that these ligands can be classified as being slow radical scavengers, just like the 1-hydroxypyridin-2(1H)-ones 2 and 3. 28,43 The calculated EC 50 values (Table 2) showed that ligands 6a, 6c, 6d and 11a have a similar radical scavenging capability, while ligand 10a exhibited a 4 to 5 times lower EC 50 value, which is slightly better than the commercial ligand DFP 1 (EC 50 = 0.008 mg mL −1 = 5.8 × 10 −5 M) and comparable to multifunctional metal chelators containing phenol antioxidant moieties. 44 Somewhat surprisingly, ligand 6d was no better than the other ligands in this assay despite its added phenol moiety.…”
Section: Distribution Coefficientsmentioning
confidence: 94%
“…1) are also promising iron chelators in cell culture models of PD in vitro. 27,28 Compounds 2 and 3 reduced intracellular labile iron levels in both the 6-OHDA 27 and lactacystin 28 models of PD, and restored labile iron and iron-responsive protein expression to normal levels in the 6-OHDA model of PD. 27 More recently, we showed that both compounds also reduced α-synuclein accumulation induced by the potent ubiquitin proteasomal inhibitor lactacystin.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations